2007
DOI: 10.1128/jcm.00813-07
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive p24 Antigen Assay for Diagnosis of Perinatal Human Immunodeficiency Virus Type 1 Infection

Abstract: We evaluated an ultrasensitive p24 antigen enzyme immunosorbent assay on 802 plasma specimens from 582 infants and children of 0 to 180 days of age. Overall sensitivity and specificity were 91.7% and 98.5%, respectively. After exclusion of infants of less than 7 days of age, the sensitivity and specificity were 93.7% and 98.3%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…Many studies support the use of the Perkin Ultra p24 immunoassay for early diagnosis in infants aged 10 days to 12 months. 30,36,37 p24 immunoassay Policy & practice Low-cost tools for HIV diagnosis and monitoring Grace Wu & Muhammad H Zaman of dried blood spot samples had 94.4% sensitivity and 100% specificity in another study. These findings are promising because dried blood spot analysis is common for infant diagnosis in rural areas.…”
Section: Early Infant Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies support the use of the Perkin Ultra p24 immunoassay for early diagnosis in infants aged 10 days to 12 months. 30,36,37 p24 immunoassay Policy & practice Low-cost tools for HIV diagnosis and monitoring Grace Wu & Muhammad H Zaman of dried blood spot samples had 94.4% sensitivity and 100% specificity in another study. These findings are promising because dried blood spot analysis is common for infant diagnosis in rural areas.…”
Section: Early Infant Diagnosismentioning
confidence: 99%
“…29 Several reports support the use of the EXAVir Load Version 3 nucleic acid test for HIV load monitoring in the developing world. 14,[29][30][31] In this test, a gel-separation step isolates virions from plasma components. The virions are then lysed and the lysates undergo a modified ELISA to measure the activity of reverse transcriptase.…”
Section: Hiv Load Monitoringmentioning
confidence: 99%
“…The persistence of maternal antibodies against HIV in exposed infants up to 18 months of age prevents the use of the enzyme-linked immunosorbent assay for the early diagnosis of HIV infection. Thus, approaches to the early diagnosis of infection in infants have included ultrasensitive heat-denatured p24 antigen quantitation (4,16,23) and nucleic acid amplification techniques that target HIV DNA (15), RNA (14), or total nucleic acid (3,10,18), most commonly with samples obtained at 6 weeks of age. It has also been established that the collection of blood as dried blood spots (DBSs) improves access to tests for the early diagnosis of HIV infection among infants in resource-limited settings (2,17).…”
Section: Most Human Immunodeficiency Virus (Hiv)-infected Infants Resmentioning
confidence: 99%
“…Others have suggested that p24 assays might be less specific in very young infants (24). However, we previously tested plasma samples with the Up24 assay and observed similar specificity in infants 0 to 7 days of age (1 of 109 [99%]) (11). The optimal time to use the Up24 antigen assay for infant diagnosis requires further investigation, especially as prevention of mother-to-child transmission programs in low-resource countries move to more-complex and longer postdelivery antiretroviral regimens.…”
mentioning
confidence: 99%
“…It has been used successfully with plasma for over 12 years for diagnosis of HIV infection in infants (9,11,13,18,19,26,29,32).…”
mentioning
confidence: 99%